White Matter Changes in HIV+ Women with a History of Cocaine Dependence - Wakim, Kathryn-Mary; Molloy, Ciara J.; Bell, Ryan P.; Ross, Lars A.; Foxe, John J. (Frontiers in Neurology, 2017)
Cocaine use is associated with the transmission of human immunodeficiency (HIV) virus through risky sexual behavior. In HIV+ individuals, cocaine use is linked with poor health outcomes, including HIV medication non-adherence and faster disease progression. Both HIV and cocaine dependence are associated with reduced integrity of cerebral white matter, but the effects of HIV during cocaine abstinence have not yet been explored. We used diffusion tensor imaging (DTI) to understand the effect of combined HIV+ serostatus and former cocaine dependence on cerebral white matter integrity. DTI data obtained from 15 HIV+ women with a history of cocaine dependence (COC+/HIV+) and 21 healthy females were included in the analysis. Diffusion based measures (fractional anisotropy, radial diffusivity, mean diffusivity, and axial diffusivity) were examined using tract-based spatial statistics and region-of-interest analyses. In a whole-brain analysis, COC+/HIV+ women showed significantly reduced fractional anisotropy (FA) and increased radial diffusivity (RD) in all major white matter tracts, except the left corticospinal tract for RD. The tract with greatest percentage of voxels showing significant between-group differences was the forceps minor (FA: 75.6%, RD: 59.7%). These widespread decreases in diffusion measures indicate an extensive neuropathological effect of HIV and former cocaine dependence on white matter in women with a history of cocaine dependence.